Effectiveness of Oregano and Thyme Essential Oils as Alternatives for Sulfur Dioxide in Controlling Decay and Gray Mold and Maintaining Quality of ‘Flame Seedless’ Table Grape (Vitis vinifera L.) during Cold Storage - Usama K. El-Abbasy; Mohamed A. Abdel-Hameed; Harlene M. Hatterman-Valenti; Ali R. El-Shereif; Ahmed F. Abd El-Khalek (Agronomy, 2023)
The current study was carried out over two seasons (2020 and 2021) to assess the effects of preharvest treatments with oregano and thyme essential oils (EOs) as an alternative to the traditional use of sulfur dioxide (SO2) during cold storage of grape clusters cv. Flame Seedless. Grapevines were sprayed with oregano or thyme essential oils at 2000 or 4000 µL/L two days before harvest. The results confirmed that oregano and thyme EOs treatments reduced the physiological loss in weight, decay incidence, gray mold, rachis browning index, and berry shattering as compared to sulfur dioxide and untreated fruits. In addition, EOs had higher marketable percentage, firmness, and visual appearance cluster scores, while they reduced the deterioration in titratable acidity (TA) and ascorbic acid (AsA) contents, slowing the increases in soluble solids content (SSC) and SSC/TA ratio of berries, and improving total anthocyanin content. Moreover, these EOs delayed berry activities of polyphenol oxidase (PPO), peroxidase (POX), and pectin methylesterase (PME) enzymes during cold storage. Results suggest that preharvest application with either oregano or thyme EOs at 2000 µL/L might be a promising eco-friendly and safe candidate as an alternative to conventional SO2 used to control decay incidence and gray mold rot caused by Botrytis cinerea, and the EOs were effective in maintaining the quality of grape clusters during cold storage for up to 45 days.